DC and RF characterization of InGaAs replacement metal gate (RMG) nFETs on SiGe-OI FinFETs fabricated by 3D monolithic integration. (February 2017) - Deshpande, V.; Djara, V.; O'Connor, E.; Hashemi, P.; Balakrishnan, K.; Caimi, D.; Sousa, M.; Czornomaz, L.; Fompeyrine, J.
Abstract: We report the first RF characterization of short-channel replacement metal gate (RMG) InGaAs-OI nFETs built in a 3D monolithic (3DM) CMOS process. This process features RMG InGaAs-OI nFET top layer and SiGe-OI fin pFET bottom layer. We demonstrate state-of-the-art device integration on both levels. The bottom layer SiGe-OI pFETs are fabricated with a Gate-First (GF) process with fins and featuring epitaxial raised source drain (RSD) as well as silicide contact layer. The top layer InGaAs nFETs are fabricated with a RMG process featuring a self-aligned epitaxial raised source drain (RSD). We show that the 3D monolithic integration scheme does not degrade the performance of the bottom SiGe-OI pFETs owing to an optimized thermal budget for the top InGaAs nFETs. From the RF characterizations performed (post-3D monolithic process) on multifinger-gate InGaAs-OI nFETs, we extract a cut-off frequency (Ft) of 16.4 GHz at a gate-length ( L g ) of 120 nm. Measurements on various gate lengths shows increasing cut-off frequency with decreasing gate-length.